Pediatric renal calyceal diverticular calculi: Diagnostic and management by percutaneous nephrolithotomy “case report” - Nangue Ngansob Loïs Landry; Pankaj Wadhwa; Meera Luthra; Shweta Joshi (Urology Case Reports)
Renal calyceal diverticula are rarely diagnosed in children. Calculus formation within the diverticulum is a significant complication and its management in children remains controversial. We report our experience with 1 case, managed with minimally invasive surgery.We report one pediatric case who presented with flank pain. Physical examination, biochemistry and urinalysis were normal. Contrast-enhanced computed tomography revealed calyceal diverticulum type II with secondary diverticular calculus. The patient underwent mini-percutaneous nephrolithotomy and recovered uneventfully.Percutaneous nephrolithotomy is safe and effective, and it can be offered as a first line therapy for symptomatic calyceal diverticular calculi in children.